DIMENSIUNEA ETICĂ A CONFLICTULUI DE BIBLIOTECĂ - ZAVTUR, Natalia (BIBLIOPOLIS, 2020)
The article approaches the management of conflict in the institutions, including library. It is important the identification and elimination of the ethical deviation at different level of conflict and the sistemic activity concerning the ethical education of the personal